Methodological Guideline for Integrative Land-Biodiversity-Climate Action Analysis through Ecosystem Restoration: A case for the Economics of Land Degradation Initiative - Mirzabaev, Alisher; Akramkhanov, Akmal; Umarova, Shakhzoda; Pede, Valerien (The Economics of Land Degradation (ELD) Initiative, 2025)
This methodological guide provides a framework for assessing, developing, and implementing integrative land-biodiversity-climate actions through ecosystem restoration. It focuses on leveraging synergies to enhance the efficiency and effectiveness of restoration activities. The guide highlights the need for coordinated action across the Rio Conventions to address land degradation, biodiversity loss, and climate change under constrained financing. It aims to help policymakers and practitioners identify strategies that strengthen policy coherence, streamline processes, and optimize investments to achieve multiple sustainability goals.